Functional evidence on the involvement of the MADS-box gene MdDAM4 in bud dormancy regulation in apple - Lempe, Janne; Moser, Mirko; Asquini, Elisa; Si-Ammour, Azeddine; Flachowsky, Henryk (Frontiers in Plant Science, 2024)
Over the course of the year, temperate trees experience extremes in temperature and day length. In order to protect themselves from frost damage in winter, they enter a dormant state with no visible growth where all leaves are shed and buds are dormant. Also the young floral tissues needs to withstand harsh winter conditions, as temperature fruit trees like apple develop their flower buds in the previous year of fruit development. So far, the genetic control of induction and release of dormancy is not fully understood. However, the transcription factor family of DORMANCY-Associated MADS-box (DAM) genes plays a major role in the control of winter dormancy. One of these genes is MdDAM4. This gene is expressed in the early phase of bud dormancy, but little is known about its function. Six transgenic apple lines were produced to study the function of MdDAM4 in apple. For plant transformation the binary plasmid vector p9oN-35s-MdDAM4 was used that contains the coding sequence of MdDAM4 driven by the 35S promoter. Transgenicity of the lines was proven by PCR and southern hybridization. Based on siRNA sequencing and phenotypic observations it was concluded that line M2024 overexpresses MdDAM4 whereas the gene is silenced in all other lines. Phenotyping of the transgenic lines provided evidence that the overexpression of MdDAM4 lead to an earlier induction and a later release of dormancy. Silencing this gene had exactly the opposite effects and thereby led to an increased duration of the vegetation period. Expression experiments revealed genes, that were either potentially repressed or activated by MdDAM4. Among the potentially suppressed genes were several homologs of the cytokinin oxidase 5 (CKX5), five LOX homologs and several expansins, which may indicate a link between MdDAM4 and the control of leaf senescence. Among the potentially activated genes is MdDAM1, which is in line with observed expression patterns during winter dormancy. MdDAM2, which shows little expression during endodormancy also appears to be activated by MdDAM4.Overall, this study provides experimental evidence with transgenic apple trees for MdDAM4 being an important regulator of the onset of bud dormancy in apple.